The Karkheh River Basin: the food basket of Iran under pressure - Ahmad, Mobin-ud-Din; Giordano, Mark (Informa UK Limited, 2010)
Development of the Karkheh's water resources has contributed in important ways to Iran's food security and underpinned the livelihoods of both basin farmers and urban consumers. However, the linkages between poverty and agricultural water use in the basin are now weak at best. Furthermore, there is now little if any additional water to develop. As a result, future water policy will need to increasingly focus on management and allocation of existing resources rather than development of new sources of supply, and poverty reduction strategies may need to aim outside agricultural water solutions.